Oral exposure of fusarenon-X induced apoptosis in Peyer's patches, thymus, and spleen of mice. (October 2015) - Aupanun, Sawinee; Poapolathep, Saranya; Imsilp, Kanjana; Prapong, Teerasak; Poapolathep, Amnart
Abstract: ICR male mice were orally administered once daily with Fusarenon-X (FX) at 0, 0.1, 0.3, and 0.5 mg/kg body weight for 14 days, and examined at 3, 6, 12, 24, and 48 h after last treatment (HAT) on Day 14. FX did not affect body and organ weight, however, at the higher doses FX caused nuclear condensation and fragmentation of lymphocytes in the cortical thymus and germinal center of Peyer's patches. Such effects were not observed in the liver, kidney and brain. Apoptotic lymphocytes evaluated by modified TUNEL method showed dose-dependency and peaked at 12 HAT in the Peyer's patches and thymus of 0.3 and 0.5 mg/kg FX-treated mice, whereas apoptotic bodies engulfed by macrophage were clearly seen by electron microscopy in 0.5 mg/kg FX-treated mice. Thus, repeated exposure to low doses of FX induces apoptosis in the lymphoid tissues of mice but did not affect liver, kidney and brain. Highlights: No mortality or clinical signs were observed during 14-day repeated exposure of low doses of FX in mice. Cortical thymus and germinal center of the Peyer's patches were most affected by 14-day repeated treatment with FX. Low doses of FX caused lymphocyte apoptosis in lymphoid organs in a dose dependent manner.